Cerebrospinal fluid and plasma procalcitonin for the diagnosis of neonatal bacterial meningitis. (2nd June 2022) - Dutta, Sourabh; Sachdeva, Naresh; Pal, Arnab; Ray, Pallab
Abstract : Aim: There is a paucity of data on cerebrospinal fluid (CSF) procalcitonin (PCT) to diagnose neonatal meningitis. We evaluated CSF PCT to diagnose bacterial meningitis among neonates with suspected sepsis. Methods: Neonates undergoing lumbar puncture (LP) as part of sepsis workup were included. Index Tests : CSF PCT, plasma PCT, CSF:plasma PCT ratio and CSF cytochemistry. Reference Standards : 'Definite meningitis' defined by positive CSF culture and/or gram stain and/or broad‐based primer 16S rDNA polymerase chain reaction. 'Definite or probable' meningitis is defined as definite meningitis or abnormal cytochemistry. Results: Of 216 eligible neonates, 18 had 'definite meningitis' and 37 'definite or probable meningitis'. Median ( Q 1, Q 3 ) CSF PCT level was significantly higher in 'definite meningitis' compared to 'no definite meningitis' (0.429 (0.123, 1.300) vs. 0.181 (0.119, 0.286) ng/mL respectively, P  = 0.028). Likewise, it was significantly higher in 'definite or probable meningitis' compared to no meningitis (0.245 (0.136, 0.675) vs. 0.170 (0.116, 0.28), P  = 0.01). The area under the receiver operator characteristics curve of CSF PCT level for definite meningitis was 0.656 and for 'definite or probable meningitis' 0.635. Paired comparisons of area under the receiver operator characteristics curve of CSF PCT with the other index tests showed no significant differences. Based on a priori cut‐off of 0.2 ng/mL, CSF PCT level had a sensitivity (95% confidence interval) of 67% (50, 80), specificity 58% (54, 61), LR + 1.6 (1.1, 2.0) and LR − 0.6 (0.3, 0.9). Conclusions: Higher values of CSF PCT are associated with neonatal bacterial meningitis. However, the diagnostic performance of CSF PCT is modest and not significantly different from standard tests.